Development of Pamukkale Piano Learning Style Scale - Serhat Süral; Serkan Demirtaş (International Journal of Assessment Tools in Education)
In musical instrument training, piano has beentaught as a compulsory instrument in all departments of Music Education. It isthought that as a major instrument, piano plays a crucial role in musiceducation. Without question, it is highly vital to raise individuals' awarenessof learning styles towards learning piano in effort to practice piano coursesmore efficiently and effectively. In this respect, the present study is ofutmost importance as it will be a pioneer study and make a great deal of contributionsto the relevant field. The current study was designed to develop a valid andreliable scale. The population of the study consisted of 170 music teachercandidates majoring in Music Education, including those who already took pianolessons. Although the study successfully accessed to the whole sample, only 133scales were included to the research, due to inaccurate or incomplete data insubjects’ responses. To test the construct validity of the scale, explanatoryfactor analysis (EFA) and confirmatory factor analysis (CFA) were used. Theoriginal scale consists of foursub-dimensions, namely, independent, analytical, dependent and affectivelearning styles.